Tuning the sound speed in macroporous polymers with a hard or soft matrix. Issue 25 (7th June 2017) - Kovalenko, Artem; Fauquignon, Martin; Brunet, Thomas; Mondain-Monval, Olivier
Abstract : Sound wave propagation in porous polymers can be controlled by tailoring the porosity and mechanical properties of the matrix. Abstract : In this paper, we investigate the factors affecting the sound speed in air-filled macroporous polymer materials at ultrasound frequencies. Due to the presence of large proportion of gas, these porous materials present high compressibility and, as a consequence, low sound speed which may fall down to values as low as 40 m s −1 . Using an emulsion-templating method, we synthesize macroporous samples with similar porous structures but with three different matrices, i.e. a hard poly(styrene-divinylbenzene (DVB)) matrix, a soft epoxy-modified polydimethylsiloxane (PDMS) matrix and a very soft polyaddition PDMS matrix. We characterize the matrix mechanical properties by measuring both the bulk modulus K 0 and the shear modulus G 0 . Next, we compare the sound speed measured in porous samples with porosity varying from 0 to 50%. We show that, in agreement with theoretical predictions, the sound speed is mainly controlled by two parameters, the porosity value and the K 0 / G 0 ratio of the polymer matrix. These parameters may be used to control the sound propagation in porous polymers, which opens the way to the realization of gradient-index materials.